Decision-Based Disorders: The Challenge of Dysfunctional Health Behavior and the Need for a Science of Behavior Change. (March 2017) - Bickel, Warren K.; Pope, Derek A.; Moody, Lara N.; Snider, Sarah E.; Athamneh, Liqa N.; Stein, Jeffrey S.; Mellis, Alexandra M.
Dysfunctional health behavior is a contemporary challenge, exemplified by the increasingly significant portion of health problems stemming from people's own behavior and decision making. The challenge not only includes the direct consequences of unhealthy behavioral patterns but also their origins and the creation of policies that effectively decrease their frequency. A framework rooted in behavioral economics identifies the processes and mechanisms underlying poor health. Two behavioral economic processes, economic demand and delay discounting, are discussed in detail. Through continued development, this behavioral economic framework can guide improved outcomes in treatment and policies related to dysfunctional health behavior. Approaches are evolving to alter demand and discounting. Current and prospective policies aimed at decreasing unhealthy behavior may profit from such research.